The Emergence of Hasidic Literature: A Reexamination - Moseson, Elly (The Jewish quarterly review, 2026)
This study reexamines the emergence and development of Hasidic literature and reassesses its relationship with the Hasidic movement. A comprehensive review of extant manuscripts and printed sources pertaining to the earliest writings associated with the movement challenges their traditional attribution mainly to Dov Ber, the Maggid of Mezritsh, revealing them instead as the product of a prolonged, collective, and largely anonymous literary enterprise. In addition to discourses of the Maggid transcribed by some of his disciples, this corpus includes an influential work composed by an anonymous disciple of the Israel Ba‘al Shem Tov (the Besht) as well as substantial later material stemming from the Maggid’s circle. This study further explores the reception and influence of these early writings, their role in the anti-Hasidic controversies, and the ambivalence displayed toward them by some Hasidic leaders. By reassessing the nature and origins of the earliest corpus of Hasidic writings and uncovering its various components and layers, this essay sheds new light on the complex role played by literature in the transformation of Hasidism from a small local phenomenon into a mass movement.